물리치료사의 임파워먼트와 직업전문성이 직무만족도에 미치는 영향 - 김성환; 유성훈 (대한정형도수물리치료학회지, 2023)
Background: This study examined the relationship between the empowerment, and occupational professionalism of physical therapists, and the factors affecting their job satisfaction. Methods: The subjects of the study were 240 physical therapists who had worked at medical institutions for more than a year. Data were collected from April 1 to 30, 2022. Results: The mean scores for job satisfaction, empowerment, and occupational professionalism were 3.43±.52, 3.60±.60, and 3.74±.40 points, respectively. Empowerment was positively correlated with occupational professionalism (r=.75, p<.001) and job satisfaction (r=.59, p<.001). Also, occupational professionalism was positively correlated with job satisfaction (r=.68, p<.001). The factors influencing job satisfaction were empowerment (β=.17, p<.05) and occupational professionalism (β =.56, p<.001), showing an explanatory power of 48%. Conclusions: The results of this study revealed that the higher the empowerment and occupational professionalism, the higher the job satisfaction of physical therapists. To improve their job satisfaction, it is, therefore, necessary to develop and apply an effective program to improve their empowerment and occupational professionalism level. These research results can be useful as basic data for improving the job environment of these therapists and the policies relating to their work.